ENHANCING MARITIME SHIPPING OPERATIONS DECISION-MAKING IN A FERTILIZER COMPANY THROUGH A DYNAMIC DASHBOARD: A QUALITATIVE CONTENT ANALYSIS - Edwin Octoriza (CV. RADJA PUBLIKA, 2025)
This research examines how a dynamic dashboard can enhance decision making process in PT Pupuk Indonesia’s maritime fertilizer distribution system and identifies the performance metrics required to be embedded in the dashboard. The study employs a qualitative research methodology by using semi structured interviews with three key stakeholders from the Distribution Compartment: the Senior Vice President of Distribution, the Vice President of Distribution Planning and Controlling, and an Officer of Shipping Operations. The interview data were analyzed using Johnny Saldaña’s (2009) First Cycle and Second Cycle coding techniques to systematically generate insights and derive thematic conclusions. The analysis reveals that current decision making process rely heavily on fragmented information and partially manual workflows, resulting in inconcistencies and limited visibility. Existing digital system does not provide enough operational level metrics and this study highlights the need for data integration across functions and subsidiaries, real time updates, and standardized operational KPIs to be embedded to support decision making.